Molecular dynamics study on the effect of minerals on the mechanical heterogeneity of anthracite coal：A case study of kaolinite in the southern part of the Qinshui Basin - Bin ZHANG; Beilei SUN; Dezhang WANG; Tianhe KANG; Xin MA; Xiaoyu ZHANG; Ligong LI; Haoyang LI; Xiaomin LIANG; Wenqing ZHU; Junshuang ZHANG (Meitan xuebao, 2024)
Coal is a mixture of organic macerals and minerals. The presence of minerals can lead to differences in the macromolecular structure of coal, resulting in significant heterogeneity in its mechanical properties, which in turn affects the overall coalbed methane production, fracturing and transformation effects, and the large-scale application of mature technologies within the block. Taking typical anthracite and kaolinite minerals from the Qinshui Basin as the research object, the influence of kaolinite and its content on the mechanical properties of anthracite is quantitatively studied through molecular dynamics methods. The molecular structure and pore characteristics of anthracite under different mineral contents are analyzed, and its microscopic mechanism is revealed from the perspective of energy and ordering. The results indicate that: ① There are both van der Waals forces and hydrogen bonding forces during the binding process between coal organic matter and kaolinite, and the intensity of hydrogen bonding is higher than that of van der Waals forces. The probability, interaction strength, and orderliness of kaolinite molecules appearing around coal organic matter increase with the increase of mineral content. ② The porosity of anthracite decreases linearly with the increase of kaolinite content, with φ=−0.229 3a+9.629 5, while the bulk modulus, elastic modulus, and shear modulus of anthracite all increase linearly with the increase of kaolinite content. The Poisson’s ratio decreases exponentially with the increase of kaolinite content. ③ The degree of mechanical heterogeneity of anthracite increases overall with the increase of kaolinite content. The variability of bulk modulus, elastic modulus, and shear modulus under different kaolinite contents can be divided into five parts: very low, low, medium, high, and very high. The coefficient of variation of Poisson's ratio is all less than 0.1, indicating very low variability. ④ As the content of kaolinite increases, the interaction energy between coal organic matter and kaolinite shows a linear increase (Einteraction=4.558 5a+443.929). Compared with pure organic matter, when the content of kaolinite reaches 20%, the bond energy and van der Waals energy of anthracite increase by 63.86% and 48.06%, respectively. ⑤ The internal reason why kaolinite enhances the mechanical properties of coal is that it occupies a certain pore space after entering the coal organic matter and interacts with the aromatic carbon skeleton and different functional groups of the coal organic matter. The higher the content of kaolinite, the greater the degree of filling the pores of the coal macromolecular structure and the energy of the coal macromolecular structure, resulting in a decrease in the porosity of the coal macromolecular structure, an increase in orderliness, and an increase in mechanical strength and resistance to deformation.